Penerapan Model Teams Games Tournament untuk Meningkatkan Proses dan Hasil Belajar Keterampilan Berbicara - Abdul Halik; Nur Ilmi; Juli Astria Ningsih (STKIP Andi Matappa Pangkep, 2023)
The problem in this study is the low learning outcomes of class V students' speaking skills so that action is needed. The approach used is a qualitative approach and the type of research used is Classroom Action Research (PTK). The subjects in this study were fifth grade students of UPT SD Negeri 9 Arawa Sidrap Regency for the 2022/2023 academic year, with a total of 15 students consisting of 7 male students and 8 female students, as well as a teacher. The focus of this research is the focus on the process and the focus on the learning outcomes of students' speaking skills about pantun by applying the cooperative learning model of the team games tournament type. Data collection techniques used in this study include the stages of observation, testing and documentation. The data analysis technique used was data reduction, data condensation, data presentation and conclusion which were processed qualitatively. The conclusions in this study are that the process and learning outcomes of students' speaking skills in class V UPT SDNegeri 9 Arawa, Sidrap Regency by applying the cooperative learning model of the team games tournament type have increased.